Ethical risks in robot health education: A qualitative study - Mei, ZiQi (Nursing ethics, 2025)
BackgroundAs health education robots may potentially become a significant support force in nursing practice in the future, it is imperative to adhere to the European Union’s concept of “Responsible Research and Innovation” (RRI) and deeply reflect on the ethical risks hidden in the process of intelligent robotic health education.AimThis study explores the perceptions of professional nursing professionals regarding the potential ethical risks associated with the clinical practice of intelligent robotic health education.Research designThis study adopts a descriptive phenomenological approach, employing Colaizzi’s seven-step method for data analysis.Participants and research contextWe conducted semi-structured interviews with 17 nursing professionals from tertiary comprehensive hospitals in China.Ethical considerationsThis study has been approved by the Ethics Committee of the Second Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Provincial Second Chinese Medicine Hospital.FindingsNursing personnel, adhering to the principles of RRI and the concept of “person-centered” care, have critically reflected on the potential ethical risks inherent in robotic health education. This reflection has primarily identified six themes: (a) threats to human dignity, (b) concerns about patient safety, (c) apprehensions about privacy disclosure, (d) worries about implicit burdens, (e) concerns about responsibility attribution, and (f) expectations for social support.ConclusionsThis study focuses on health education robots, which are perceived to have minimal ethical risks, and provides rich and detailed insights into the ethical risks associated with robotic health education. Even seemingly safe health education robots elicit significant concerns among professionals regarding their safety and ethics in clinical practice. As we move forward, it is essential to remain attentive to the potential negative impacts of robots and actively address them.